Nuclear form factors and closure approximation in the study of the (μ-,e-) conversion in nuclei - Kosmas, T. S.; Vergados, J. D. (HNPS Advances in Nuclear Physics, 2020)
The methods of studying the exotic (μ-,e-) conversion in nuclei are discussed. For the coherent process the dependence of the rate on the nuclear parameters is obtained by using shell model nuclear form factors. For the noncoherent processes the relevant matrix elements are calculated in the framework of the closure approximation. Finally the fraction of the transition rate of the coherent process throughout the periodic table is calculated.